2018
DOI: 10.1016/j.bbmt.2017.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Toxicity of Pharmacokinetic (PK)-Directed Dosing of Evomela® (propylene glycol free melphalan, PGF-MEL) for Multiple Myeloma (MM) and AL Amyloidosis (AL) Patients Undergoing Autologous Hematopoietic Stem Cell Transplant (AHCT)

Abstract: point in the gut microbiome and was not detected at baseline and at T+30. At the genus level, in oral wash samples, Haemophilus parainfluenzae abundance significantly decreased between T-2 and T+7 (P = .01) and subsequently increased at T+30 (P = .005). In the gut microbiome, Desulfovibrio D168 species significantly decreased from baseline to T+7 (P = .03). Conclusion and Future Directions: Microbial composition and bacterial diversity is altered significantly during HCT, with the lowest diversity noted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…38 Further, several recent studies have demonstrated the feasibility of using pharmacokinetic-directed dosing of PG-free MEL to optimize serum melphalan concentrations. 24, 39 Future prospective studies should clarify these findings and investigate if this method could be used to improve ASCT outcomes while sparing patients of undue toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…38 Further, several recent studies have demonstrated the feasibility of using pharmacokinetic-directed dosing of PG-free MEL to optimize serum melphalan concentrations. 24, 39 Future prospective studies should clarify these findings and investigate if this method could be used to improve ASCT outcomes while sparing patients of undue toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a split-dosing schema starts at an initial dose of 100 mg/m 2 with PK monitoring and increasing the second dose proportionately based on first-dose PK to achieve the desired level of exposure. Shah et al [21] reported early results with a 10-mg/m 2 test dose and subsequent PK-based dosing. Although the collection of PK and calculation of a target dose was feasible using results from the test dose, the target AUC could not be achieved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be increasing enthusiasm for intensifying the preparatory regimen in MM using other approaches, including 2 randomized phase II studies comparing bendamustine and melphalan [22] as well as BEAM (carmustine, etoposide, cytarabine, Melphalan) (NCT03570983) to Mel200 in addition to the above mentioned PETHEMA-GEM study comparing BuMel to Mel200 [16] . Similar to our work with busulfan, pharmacokinetic based melphalan dosing which was once thought not feasible is being explored utilizing propylene glycol free melphalan (Evomela) [23], [24] . Finally, the incorporation of proteasome inhibitors into the preparatory regimen is particularly attractive as they have been shown to enhance the sensitivity of multiple myeloma tumor cells to chemotherapeutic agents without affecting normal hematopoietic cells [25] .…”
Section: Progression Free Survival Toxicitymentioning
confidence: 99%